2020
DOI: 10.1007/s00586-020-06473-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction tool for pain reduction in adult patients undergoing elective lumbar spinal fusion: a multicentre cohort study

Abstract: Purpose On average, 56% of patients report a clinically relevant reduction in pain after lumbar spinal fusion (LSF). Preoperatively identifying which patient will benefit from LSF is paramount to improve clinical decision making, expectation management and treatment selection. Therefore, this multicentre study aimed to develop and validate a clinical prediction tool for a clinically relevant reduction in pain 1 to 2 years after elective LSF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…For satisfaction, it ranged from 0.60 (DDD) to 0.66 (LDH). Other reports with PROMs as outcome measure and logistic regression as analytic method describe AUC values and c-indexes ranging from 0.64 to 0.79, mostly tested on singlecentre cohorts [5,6,9,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For satisfaction, it ranged from 0.60 (DDD) to 0.66 (LDH). Other reports with PROMs as outcome measure and logistic regression as analytic method describe AUC values and c-indexes ranging from 0.64 to 0.79, mostly tested on singlecentre cohorts [5,6,9,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…org Patient-centred outcome prediction is a growing focus in spine research, producing several reports annually. The majority discuss prediction in terms of Patient-Reported Outcome Measures (PROMs) [5][6][7][8][9][10][11][12][13][14][15], a few deals with adverse events [16,17], length of stay [18], revision surgery [19] or return to work [20]. Among the PROM analyses, the outcome measure is usually dichotomized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hopes of being able to predict the effects of fusion surgery more robustly by generating "objective" risk-benefit profiles for each individual patient have not been fulfilled to date [26]. Janssen et al [27] achieved an externally validated AUC of 0.68 for prediction of MCID in the predominant pain complaint using a nomogram. Apart from this nomogram, to our best knowledge, the only other externally validated prediction tools that predict pain and functional outcomes for this population are the prediction models of Khor et al [14].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, patients eligible for LSF are often divided into subgroups by their medical diagnosis, in order to estimate the success probability after surgery [9]. Previous research showed various risk factors are also important to consider when estimating a person's postoperative outcomes after LSF: male gender, young age, working people, non-smokers and high income are predictors of a good outcome [10,11]. However, relying on these variables alone to categorize patients into risk profiles foregoes other important information related to postoperative success chance, as the population undergoing LSF is rather heterogeneous.…”
Section: Introductionmentioning
confidence: 99%